Prácticas de crianza parentales y la autoestima en niños de la institución educativa inicial N°639 San Isidro, San Pablo 2024 - Castillo Piña, Priscilla Patricia (2024)
The objective of this research is to determine the relationship between parental parenting practices and self-esteem in children of the Initial Educational Institution N°639 San Isidro San Pablo 2024; The research approach is based on the quantitative approach, non-experimental research type, of correlational transactional design. The population under study is made up of all children, totaling 144 children. To obtain data, the observation technique was used and an observation guide was used as an instrument, which have been validated by three experts on the subject. For the reliability of the instruments, they were evaluated with a pilot test, using the Cronbach's Alpha test, resulting in the Spearman's Rho correlation coefficient between the parenting practice and the children's self-esteem. The correlation coefficient is 0,735, which indicates a moderate to high positive correlation between both variables. Furthermore, the significance value (p = 0,05) is equal to the significance threshold, concluding that the null hypothesis is rejected. This implies that there is a significant relationship between the parenting practice and self-esteem in the children of the Initial Educational Institution N°639 San Isidro San Pablo. Therefore, the general hypothesis is accepted